Reconciling river basin management and environmental preservation: some perspectives from the Krishna Basin, South India - Venot, Jean-Philippe; Sharma, Bharat R.; Rao, K.V.G.K. (2009)
Basin water development, rural dynamics and the institutional setting of natural resources management in the Krishna basin have led to a degradation of downstream ecosystems manifesting itself by salinizing soil and groundwater, increasing pollution, disappearing mangroves and desiccating wetlands. Reversing this evolution requires the formal recognition of the environment as a water user in its own right and the implementation of an environmental water provision that should be based on a two-tier allocation system, with assured discharges in the irrigation canals of the delta and to the ocean, for both sustaining local livelihoods and preserving local ecosystems. This will lead to further commitment of water resources but river basin closure (zero or minimal flow to the ocean) increases the likeliness of a re-allocation of water: this reallocation is likely to be driven by economic and political motives and high attention is to be given to equity and environmental preservation principles when allocating water. Other measures facilitating integrated natural resources management from the local to the basin level are needed too.